WHY DO VIETNAMESE PEOPLE EVADE TAXES? - Nguyen, Thu Hang (Journal of International Economics and Management, 2018)
Prior works and theoretical framework has shown many determinants to tax evasion. However, the authors did not examine which determinants are the most and the least important reasons for evading taxes from taxpayers’ perspective. This study examines the importance levels of reasons why people evade taxes, taking Vietnamese personal income tax as the case study. Data is gathered through survey questionnaire and interviews, and analyzed using Statistical Package for Social Science (SPSS) software. Results suggest that government performance related reasons are more important than deterrence related ones in explaining for people’s decision to evade taxes.